Perinatal Outcome among Women with Gestational Diabetes Mellitus - Jwan Mohammed Sabir Zangana; Nawshad Nawzad Ramadhan (Advanced Medical Journal)
Background & Objectives: Diabetes in pregnancy is associated with an increased risk of complications in both the mother and the fetus. Early diagnosis by the screening of pregnant women between 24 to 28 weeks of gestation with proper control of diabetes is important to reduce the adverse effects in perinatal outcomes. This study aims to know the perinatal outcome among neonates of diabetic mothers in comparison with those of non-diabetic mothers.